PECULIARITIES OF POLITICAL SECURITY OF UKRAINE IN CONDITIONS OF MODERN CHALLENGES - Kruhоvyi D. Dmytro (Theory and Practice of Public Administration, 2020)
The article highlights the peculiarities of becoming a political security of the Ukrainian state at the present stage of development. It is noted that political security is a stable state and effective development of the political system of society, which allows to adequately respond to negative internal and external actions, to preserve the integrity of the society and its essential qualities. Political security is aimed at protecting social groups, achieving internal political stability and reducing social tension. Threats and challenges facing Ukrainian society are highlighted. Emphasis is placed on the importance of developing and implementing an effective national security policy in the domestic sphere. Criteria that reflect the level of internal political stability are identified Institutional support for political security is being explored. It is stated that the key link in the area of securing the planning and forecasting of the security system and the area of protection is the national security and defense. Attention is drawn to the fact that one of the leading bodies in the field of political security is the Security Service of Ukraine, which is a state special-purpose body with law enforcement functions that ensures state security, exercising steadily respect for human and citizen’s rights and freedoms. It is noted that in order to ensure internal political stability and prevent social tensions, active monitoring of threats to the security of the individual, society and the state should be constantly carried out, and on that basis, the development of appropriate national security policy and its timely implementation. It is emphasized that an important prerequisite for ensuring political security is overcoming corruption, creating the right conditions for the development of small and medium-sized businesses, the formation of the middle class, increasing the opportunities for education, social security, employment of the population, achieving the proper level of material well-being of Ukrainians and social protection of the population.